ANALISIS FAKTOR – FAKTOR PEMILIHAN PEMENANG LELANG JASA KONSTRUKSI PADA PROYEK PEMERINTAH DI KABUPATEN SIKKA - Nong Pio, Gaudensius; Sutarja, I N.; Yansen, I W. (JURNAL SPEKTRAN; Vol. 3, No. 2, Juli 2015DO - 10.24843/SPEKTRAN.2015.v03.i02.p08, 2015)
This study aims to determine the factors that influence the selection of the winning bidder in the construction of government projects in Sikka district and determine the most dominant factors. The sample in this study was 57 respondents. Sampling was conducted using a non-probability sampling technique with purposive sampling. Data analysis was performed by factor analysis.   The results of the study obtained 4 factors that influenced the selection of the winning bidder with 84.004% cumulative variance. Factors that influenced were the dominant factor I from 15 variables namely, completeness and suitability of substantial terms requested in the bidding documents; the experience of the company/contractor; bank reference/support of banks; completeness and availability as well as the number of different types of tools/equipment/construction equipment; the availability of education and experience of personnel/field project staff; relationship/ proximity to the project owner; the validity and completeness of the offer letter; the validity of a business license; a contractor offers had to be the lowest prices and the detailed points were competitively priced; meeting tax obligations; the company was not in the custody of the court and was not included in the black list; the contractor would follow and respond quickly to requests; instructions and orders of the project owner for the repair/construction design changes; originality, suitability and validity of bid security letters; methods and strategies for the use and control of the work; the contractor completed the work in accordance with the quality required and in accordance with the specifications of the contract price.
Keywords: Procurement of Construction Services, Construction Project, Factor Analysis.